Innovative R&D and Optimal Investment under Uncertainty in High-Tech Industries : An Implication for Emerging Economies - Tsai, Yingyi (2012)
In order to continue on the path to convergence with advanced countries, emerging countries need to strengthen their research capabilities. Often they try to do this through the development of strategic industries. The objective of this paper is to contribute to the debate on the effectiveness of policies aimed at the development of strategic industries in emerging economies. The paper develops a three-phase model for product innovation with capital investment under uncertainty to study the investment decisions of a manufacturer in an industry facing a volatile market demand for new inventions. The findings demonstrate the importance of interactions between market structure, a firm's market power and the associated cost of adjustment. The paper draws out implications for emerging economies with regard to policies striving to develop strategic industries in sectors such as semiconductors and information technology.